Integrating management of marine activities in Australia. (1st March 2023) - Stephenson, Robert L.; Hobday, Alistair J.; Butler, Ian; Cannard, Toni; Cowlishaw, Mel; Cresswell, Ian; Cvitanovic, Christopher; Day, Jon C.; Dobbs, Kirstin; Dutra, Leo X.C.; Frusher, Stewart; Fudge, Maree; et al.
Abstract: Integrated management (IM) has been widely proposed, but difficult to achieve in practice, and there remains the need for evaluation of examples that illustrate the practical issues that contribute to IM success or failure. This paper synthesises experiences of academics and practitioners involved in seven Australian case studies in which there have been attempts to integrate or take a broader, holistic perspective of management. The evaluative framework of Stephenson et al. (2019a) was used as a lens to explore, through workshops and a questionnaire survey, the nine key features and five anticipated stages of IM in the Gladstone Harbour Project, the Great Barrier Reef, the Northern Prawn fishery and regional development, the South-East Queensland Healthy Waterways Partnership, the Australian Oceans Policy, the New South Wales Marine Estate reforms, and progress toward Integrated Management in the Spencer Gulf. Workshops involving experts with direct experience of the case studies revealed that most of the key features (recognition of the need; a shared vision for IM; appropriate legal and policy frameworks; effective process for appropriate stakeholder participation; comprehensive suite of objectives (ecological, social, cultural, economic and institutional); consideration of trade-offs and cumulative effects of multiple activities; flexibility to adapt to changing conditions; process for ongoing review, evaluation and refinement; and effective resourcing) were seen as important in all case studies. However, there are only a few examples where key features of IM were implemented 'fully'. A subsequent questionnaire of participants using 'best-worst' scaling indicated that an appropriate legal and institutional framework is considered to have most influence on IM outcomes, and therefore is the most important of the key features. This is followed in salience by effective stakeholder participation, effective resourcing, capacity and tools, and recognition of the need for IM. Key features may change in relative importance at different stages in the trajectory of IM.